Minimally invasive exoscope-assisted coccygectomy: A novel approach for chronic refractory coccydynia - Barnabas Obeng-Gyasi; Danielle Wilmes; Matthew P. Blackwell; Jae H. Kwon; Gordon Mao (World Neurosurgery: X)
Background: This technical note presents a novel minimally invasive exoscope assisted coccygectomy to treat chronic refractory coccydynia. Traditional treatments often fail to provide adequate relief for this debilitating condition, prompting the need to explore surgical approaches. Case Description: A 40-year-old female patient with persistent pain unresponsive to conservative treatments underwent this advanced procedure. Utilizing the Synaptive exoscope-microscope system, the surgery allowed for precise dissection and removal of affected coccygeal segments, with a focus on minimizing skin and soft tissue disruption to optimize wound healing and surgical site pain. Conclusion: Postoperative recovery showcased significant pain reduction and improved quality of life, emphasizing the method's potential for better outcomes and fewer complications. Despite the promising results, the limitations of a single-case study necessitate further research to establish long-term effectiveness across a broader patient population.